Peningkatan Produktivitas Tomat (Lycopersicum esculentum Mill.) pada Tanah Aluvial dengan Pemberian Trichokompos dan Pupuk Kalsium - Ardianti, Wiwik; Tris Haris Ramadhan, Tris Haris Ramadhan; Wasi'an (Jurnal Hortikultura Indonesia, 2025)
Alluvial soil management to increase tomatoes growth and yield is faced with low physical, chemical, and biological soil quality. Improvement of alluvial soil quality can be achieved by providing organic materials enriched with microorganisms and fertilization for nutrient supply for plants. The study aims to determine the role of trichocompost based of goat manure and calcium fertilizer in increasing tomatoes productivity. The study was conducted in Singkawang City, West Kalimantan. The research from April to June 2024. A factorial randomized block design was used to organize the field research. The first factor is the dose level of trichocompost (without trichocompost, 10 tons ha-1, and 20 tons ha-1). The second treatment was the dosage level of calcium fertilizer (without calcium fertilizer, 5, 10, 15, and 20 g L-1). The results showed trichocompost and calcium fertilizer can increased the growth and yield of tomatoes on alluvial soil. Calcium fertilizer 5 g L-1 and trichocompost 2 ton ha-1 were optimal in increasing the growth and yield of tomatoes. The interaction of 10 g L-1 calcium fertilizer and 2 tons ha-1 trichocompost was able to increase the number of fruits 38.50 fruits and the fruit weight per plant 1514.38 g. Keywords: microorganisms, plant nutrition, soil fertility, tomatoes yield